(3GdGSJZGKI HCgd Gddgs - (3GdSQZjfj , eMeO Hf eMeO Hf GdeYWj GdSQZjfj GdeDbJ GdeQGcTj, CHh YHO Gddg,J (B1329 (3g` s
(3ChdgG (B:s
(3Edjc CHG jYbhH QaY TcjJi CjhSa Efi ai MeGce ONdJ MeGce aEfgVhG dMejJi ajG QLGd Gddg jeGPG SDGd s
(3BNQgG (B:s
(3LhOG Ydi GdCgd hGdCUMGH HGdeff jG SGOI dge GdJNUjU ai GdCRd hde jQM HghGjG GdCgd hGdNhd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B77 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B305s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdeLGejYs